The English Language in University Curriculum: Importance, Challenges and Achievements - España Chavarría, Carolina (2010)
The importance of English language inclusion into university’s curriculum is based on the demands of globalization and market interchanges, that is why English language must be considered as part of students’ instruction as future professionals that will contribute to the integral development of the nation.